Coordinated Control of Interconnected Microgrid and Energy Storage System - Md. Asaduz-Zaman; Md. Habibur Rahaman; Md. Selim Reza; Md. Mafizul Islam (Institute of Advanced Engineering and Science, 2018)
Several microgrids can be interconnected together to enhance the grid reliability and reduce the cost of supplying power to an island area where conventional power grid cannot be connected. Source and load demand do not properly balance always. Besides that, sometimes power and frequency fluctuation has occurred in MG at island mode. Need to design a special control for maintaining the state of charge (SoC) of energy storage system. This paper proposes a new power supply system for an island area that interconnects two microgrids with a single energy storage system (ESS). An algorithm has been proposed that control the microgrids energy storage system for spinning reserve and load power/frequency regulation purpose. The minimum loading constraints of diesel engine generator (DEG) is considered and the SOC of the ESS is properly maintained.